Credit risk, management behavior and macroeconomic equilibrium in modern banking systems - Maramygin, Maksim; Kuznetsov, Nikolay; Ushanov, Alexander; Shestak, Viktor (Opción, 2019)
The aim of the work is to substantiate the strategic directions of the credit market development, which take into account the full range of legal, financial, economic, institutional, organizational and social marketing activities via methods of analysis, synthesis and generalization. It is shown that one of the ways to improve banking regulation and lending, aimed at reducing credit risks, is to establish certain quantitative standards for loan security and profitability of borrowers. In conclusion, the development of effective mechanisms for working with problem assets should be based on the creation of regulatory and legal support for asset management companies